Use of the Anterolateral Thigh and Vertical Rectus Abdominis Musculocutaneous Flaps as Utility Flaps in Reconstructing Large Groin Defects - Aslim, Edwin Jonathan; Rasheed, Mohamed Zulfikar; Lin, Fangbo; Ong, Yee-Siang; Tan, Bien-Keem (Archives of Plastic Surgery, 2014)
Background Groin dissections result in large wounds with exposed femoral vessels requiring soft tissue coverage, and the reconstructive options are diverse. In this study we reviewed our experience with the use of the pedicled anterolateral thigh and vertical rectus abdominis musculocutaneous flaps in the reconstruction of large groin wounds.Methods Groin reconstructions performed over a period of 10 years were evaluated, with a mean follow up of two years. We included all cases with large or complex (involving perineum) defects, which were reconstructed with the pedicled anterolateral thigh musculocutaneous or the vertical rectus abdominis musculocutaneous (VRAM) flaps. Smaller wounds which were covered with skin grafts, locally based flaps and pedicled muscle flaps were excluded.Results Twenty-three reconstructions were performed for large or complex groin defects, utilising the anterolateral thigh (n=10) and the vertical rectus abdominis (n=13) pedicled musculocutaneous flaps. Femoral vein reconstruction with a prosthetic graft was required in one patient, and a combination flap (VRAM and gracilis muscle flap) was performed in another. Satisfactory coverage was achieved in all cases without major complications. No free flaps were used in our series.Conclusions The anterolateral thigh and vertical rectus abdominis pedicled musculocutaneous flaps yielded consistent results with little morbidity in the reconstruction of large and complex groin defects. A combination of flaps can be used in cases requiring extensive cover.
Keywords: Groins; Surgical flap; Pedicled flap; Musculocutaneous flap